WHIRLY1 Occupancy Affects Histone Lysine Modification and WRKY53 Transcription in Arabidopsis Developmental Manner - Huang, Dongmei; Lan, Wei; Li, Danjing; Deng, Ban; Lin, Wenfang; Ren, Yujun; Miao, Ying (Frontiers in Plant Science, 2018)
Single-stranded DNA-binding proteins (SSBs) are assumed to involve in DNA replication, DNA repairmen, and gene transcription. Here, we provide the direct evidence on the functionality of an Arabidopsis SSB, WHIRLY1, by using loss- or gain-of-function lines. we show that WHIRLY1 binding to the promoter of WRKY53 represses the enrichment of H3K4me3, but enhances the enrichment of H3K9ac at region contained WHIRLY1-binding sequences and TATA box or the translation start region of WRKY53, coincided with a recruitment of RNAPII. In vitro ChIP assays confirm that WHIRLY1 inhibits H3K4me3 enrichment at the preinitiation complex formation stage, while promotes H3K9ac enrichment and RNAPII recruitment at the elongation stage, consequently affecting the transcription of WRKY53. These results further explore the molecular actions underlying SSB-mediated gene transcription through epigenetic regulation in plant senescence.